ANALISIS TEGANGAN SECARA STATIS DAN DINAMIS PADA POROS TRUK PENGANGKUT RINGAN MENGGUNAKAN METODE ELEMEN HINGGA - Muhammad Fakku Ilham Firmansyah; Ahmad Anas Arifin; Eka Marliana; Miftahul Ulum (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
The purpose of this study is to determine the structural failure that occurs in the propeller shaft model of light duty vehicles with FCD450-10, SM45C, and SCM440 material types due to static and dynamic loading. This research was conducted using a simulation-based finite element method on software. The results of static FEM simulations show that each material has its own characteristics. Based on the static stress analysis that has been carried out, the results are obtained that the FCD450-10 material is stated to be in the best condition among other materials with the smallest equivalent stress value, which is 0.34203 MPa, and has the lowest minimum shear stress value of 0.19294 MPa. The best maximum total displacement value was obtained in SCM440 material, with the smallest value of 8.3405 mm. Based on the results of the Random Vibration simulation on the directional deformation of the SCM440 material, it is stated that it is in the best condition among other materials, with the smallest maximum directional deformation value of 30.109 mm and at the equivalent stress the smallest maximum value obtained is 84,433 MPa